To find the value of "-6(-5x+4y)" if the equation is true, we need to substitute the values of x and y from the given equation.
Given: -3 - 5x + 4y = -3
We can see that "-3" is canceled out from both sides.
So, -5x + 4y = 0
Now substitute this equation back into the expression -6(-5x+4y):
-6(-5x+4y) = -6(0) = 0
Therefore, the value of -6(-5x+4y) is 0.
If minus, 5, x, plus, 4, y, equals, minus, 3−5x+4y=−3 is a true equation, what would be the value of minus, 6, left bracket, minus, 5, x, plus, 4, y, right bracket−6(−5x+4y)?
1 answer